Dyslipidemia and Associated Risk Factors among Nigerians with Hypertension - Olufisayo Gabriel Ayoade; Idongesit Umoh; Collins Amadi (Dubai Medical Journal)
Background: Abnormalities in serum lipids and lipoprotein levels with essential hypertension are vital independent causal factors for atherosclerotic cardiovascular disease (ASCVD). The coexistence of these factors has a synergistic effect in heightening the risk of cardiovascular events. The aim of the study was to evaluate the pattern of dyslipidemia among hypertensives and to determine some of its correlations in patients attending a tertiary hospital in South South Nigeria. Methods: This was a cross-sectional study conducted on 544 eligible hypertensive patients attending the Cardiology Clinic, University of Uyo Teaching Hospital (UUTH), Uyo, Nigeria, over a period of 6 months. Fasting lipids, total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were evaluated. Results: Overall, 60.0% of the hypertensive patients had dyslipidemia, with 43.4.0% having high TC, 30.3% high LDL-C, 20.8% elevated TG, and 12.9% low HDL-C, respectively. There was a significant relationship between gender and lipoproteins, with women having significantly higher lipoproteins (TC, HDL-C, LDL-C, and non-HDL-C) than men. Women also had more measures of obesity with a higher body mass index and waist circumference. TC and non-HDL had a significant association with both systolic and diastolic blood pressure (BP). Altogether, 43.4% of the hypertensives had poorly controlled BP and significantly higher atherogenic lipoproteins (TC, LDL-C, and non-HDL-C). Conclusion: This study has demonstrated the relatively high prevalence of dyslipidemia among hypertensive patient in this population. High plasma TC is the most dominant pattern of dyslipidemia. Hypertensive patients with poorly controlled BP have worse atherogenic lipoprotein values and are more likely predisposed to ASCVD.